The role of peptides as intermediates in protein metabolism - Berman, Mervyn Clive (Department of Pathology, 2020)
There is much evidence in the recent literature that peptides may be intermediates in normal protein biosynthesis. This has also been inferred from certain disease states and other conditions under which protein biosynthesis is blocked at some point, e.g. cadmium, amino acid analogues or (in bacteria) antibiotics. The literature covering this concept will be presented. The present studies have been carried out on children, who because they are suffering from chronic protein malnutrition have very much lowered rates of protein synthesis and breakdown. In this unfortunate, but natural experiment, it was hoped that some factor or factors derived from protein synthesis might be found which influenced the synthetic mechanism as a whole. Evidence from the literature has been summarized which concludes that urine, apart from being convenient to collect, is the biological fluid most likely to contain high concentrates of peptides which are released during cellular metabolism.